Exploring Diverse Substrates for Enhanced Water Splitting: Tailoring Energy Conversion and Storage through Specific Qualities with Its Limitations - Waheed, Abdul; Habibullah, H.; Irfan, Muhammad; Hassan, Ali; Habib, Benish; Abbas, Shabbar; Shafique, Muhammad Zakiullah (ASEAN Journal for Science and Engineering in Materials, 2024)
Energy can be generated from various resources, encompassing both renewable and non-renewable sources. Clean energy production can be achieved through water splitting, as the electrolysis of water is recognized as an efficient method for industrial-level energy production. To enhance the energy conversion efficiency of water splitting, effective electrocatalysts are essential. Consequently, researchers strive to develop the most efficient electrocatalysts that meet specific requirements. In this pursuit, various types of catalysts have been identified in the scientific community. Each electrocatalyst possesses distinct qualities based on categories such as metal type, cost-effectiveness, and applications. This review focuses on the recent developments in substrates and their applications, considering their variability in water splitting. Each catalyst has unique characteristics compared to others, playing a pivotal role in the realm of energy production. The discussion covers the entire spectrum, from the basics to advanced levels of substrate selection, elucidating their influence on output to achieve desirable results. Finally, potential challenges and directions for future research are explored, providing a comprehensive overview of the current state and potential advancements in the field.